The Use of Digital Comics for Improving Reading Comprehension in English as a Foreign Language: A Systematic Review - Br Kembaren, Della Primsa; Mahayanti, Ni Wayan Surya; Adnyayanti, Ni Luh Putu Era (Universitas Pahlawan Tuanku Tambusai, 2026)
Reading comprehension is a crucial skill in English as a Foreign Language (EFL) learning. However, the lack of vocabulary, low interest, and uninteresting reading materials still make it difficult for many students to comprehend English texts. Digital comics have become a promising learning medium because they combine text and visuals in an interesting way. The aim of this study is to investigate the effectiveness of digital comics in enhance the reading comprehension of EFL students. This study used a Systematic Literature Review (SLR) approach guided by the PRISMA 2020 framework. Fourteen relevant studies published between 2022 and 2026 were selected from Google Scholar, ERIC, ScienceDirect, and Manual searches. The selected studies were analyzed using narrative synthesis. The results showed that students’ reading comprehension was improved by digital comic, especially when it involves comprehending important ideas, identifying specific details, learning new vocabulary, and interpreting texts. Additionally, digital comics improved student confidence, motivation, and participation in reading activities. In conclusion, digital comics are an effective and innovative learning medium for improving reading comprehension in EFL classrooms.